Psychoanalysis from nonconformity to conformism, and back - 1. (The) Ego, the Liar - Stampa, Pietro (Quaderni di Psicologia Clinica, 2015)
The psychoanalytic tradition is deeply self-contradictory, even in Freud's work, both in terms of its social function — in favor or against the establishment, aimed to an adaptation to the dominant system of thought or to a liberal intellectual opposition to common sense and conventions, respectively — and in terms of theory of mind. This first part of the present contribution examines some paradoxical aspects of psychoanalytic discourse, with specific reference to the classical models of logic.
Keywords: psychoanalysis; logic; case of Dora.